2020
DOI: 10.1002/jbio.202000017
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cell‐specific protein delivery by optoporation with laser‐irradiated gold nanorods

Abstract: The delivery of macromolecules into living cells is challenging since in most cases molecules are endocytosed and remain in the endo‐lysosomal pathway where they are degraded before reaching their target. Here, a method is presented to selectively improve cell membrane permeability by nanosecond laser irradiation of gold nanorods (GNRs) with visible or near‐infrared irradiation in order to deliver proteins across the plasma membrane, avoiding the endo lysosomal pathway. GNRs were labeled with the anti‐EGFR (ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…These results showed that the delivery efficiency significantly increased with the assistance of functionalized AuNPs (to 20.2%), compared to the 4.33% of naked AuNPs, even with a low irradiation fluence of 1.28 J/cm 2 . However, in our previous work we found that death rate increased with the increase in the concentration of AuNPs [ 30 ], and when the concentration of AuNPs was lower than a certain amount, the viability of cells was hardly affected by the irradiation fluence [ 31 ], which is confirmed in this work, as shown in Figure 6 and Figure 7 . As shown in Figure 6 ( Table 2 ), when the lower concentration was used, we found that the loading efficiency increased with an increase in irradiation fluence, but the death rate was almost constant.…”
Section: Discussionsupporting
confidence: 85%
“…These results showed that the delivery efficiency significantly increased with the assistance of functionalized AuNPs (to 20.2%), compared to the 4.33% of naked AuNPs, even with a low irradiation fluence of 1.28 J/cm 2 . However, in our previous work we found that death rate increased with the increase in the concentration of AuNPs [ 30 ], and when the concentration of AuNPs was lower than a certain amount, the viability of cells was hardly affected by the irradiation fluence [ 31 ], which is confirmed in this work, as shown in Figure 6 and Figure 7 . As shown in Figure 6 ( Table 2 ), when the lower concentration was used, we found that the loading efficiency increased with an increase in irradiation fluence, but the death rate was almost constant.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, it has been repeatedly shown that AuNPs fragment into small pieces of several nanometers (<10 nm) after being exposed to pulsed laser irradiation. [ 25–29 ] This poses additional safety risks as small gold nanoparticles may cause genotoxic effects by intercalating with intracellular DNA. [ 30,31 ]…”
Section: Introductionmentioning
confidence: 99%
“…A VNB expands until the thermal energy from the heated NP is consumed [ 65 ], after which it collapses and induces mechanical shock waves that generate transient pores in the adjacent membrane. VNB photoporation has been reported to allow intracellular delivery of various compounds, ranging from fluorescent markers [ 2 , 4 , 66 ], over RNA-based macromolecules [ 2 , 3 , 67 , 68 ] and plasmid DNA [ 69 , 70 ] to proteins [ 71 , 72 ]. Moreover, it can do so in both adherent and suspension cells with high efficiency and low cytotoxicity [ 3 , 66 , 69 , 73 ] and it has the precision to target organelle membranes such as the nuclear envelope [ 74 ].…”
Section: Membrane Disruption-mediated Techniques For Intracellular Deliverymentioning
confidence: 99%